Modeling of volatile organic compounds dispersion from open crop residue burning - Duanpen Sirithian (2019)
© 2018, Akademi Sains Malaysia. Burning of maize residues has been considered as a significant source of air pollution in the northern region of Thailand during the dry season. This study applied CALPUFF air dispersion model to predict ambient VOC concentrations released from maize residue open burning in the study area. VOC emission data in 2014 coupled with the meteorological data from the Weather Research and Forecasting (WRF) model were used as model input data. The model was simulated during January-April to predict 24-h average VOC concentrations and dispersions over the modeling domain of 100 × 100 km 2 with 1 km grid resolution. Four VOCs including benzene, acrylonitrile, xylene, and acetaldehyde were evaluated for different burned area scenarios (100% or worst-case, 75%, 50%, and 25% maize acreage areas being burned at the same time). Predicted concentrations were compared to Thailand surveillance standards and the international ambient VOC guidelines on the 24-h average basis. The results revealed that VOC concentrations from the worst-case scenario exceeded the guidelines. Reducing burned areas could decrease the maximum VOC concentrations; however, the levels of some VOCs were still higher than the guideline values. The highest value was predicted in January due to its lower wind speed as compared to other months. Therefore, we suggested that the intermittent control scheme of zero burning should be more stringent in the study area during the burning season for reducing the impacts on air quality and public health.